Estudio de las propiedades térmicas, mecánicas morfológicas y estructurales del adobe como material biocompósito - Piñas Moya, Mc Joshua Miguel (2018)
The present work of investigation presents the study of the thermal, mechanical, morphological and structural properties of the biocomposite material widely used in construction of housing of the high Andean areas: adobe. For the development of this research, adobe blocks were fabricated, reproducing the typical conditions that rural inhabitants use for their manufacture. Additionally, the dependence of Stipa ichu (scientific name of ichu) in the biocomposite was considered. The thermal characterization of adobe was carried out using Hot Plate with Guard Apparatus performing the measurements according the ASTM C 177 Standard. This part of the work was developed in the National Center of Metrology (CENAM) of Mexico. The mechanical characterization of adobe consisted in the development of the mechanical tests of compression, bending and shearing; all of them carried out in the Material Testing Laboratory of the Faculty of Civil Engineering at the National University of Engineering. Structural and morphological properties of the biocomposite were performed using X-ray Diffraction and Scanning Electronic Microscopy, both techniques were developed in the Faculty of Sciences of the National University of Engineering. Granulometry evaluation and determination of liquid limit and plastic limit of soil, used for manufacture of adobe bricks, were performed according to ASTM D2487, finding a CL type soil (clay of low plasticity with major inorganic content). According to compression results for adobe bricks without Stipa ichu and with Stipa ichu, the average values for each case were 24,44 kg cm-2 and 24,54 kg cm-2, respectively. In the case of compression of adobe stacks without fiber and with fiber, an average value of 30,22 kg cm-2 and 26,41 kg cm-2 were obtained, respectively. These results met the minimum values indicated in Peruvian Standard E.080 for Adobes. In the case of the results of the adobe bending test without fiber and with fiber, the average value is 0,56 MPa and 0,30 MPa, respectively. These results were following the guidelines of Spanish Standard UNE.EN.196.1. Following the guidelines of the Peruvian Technical Norm in Timbers NTP 251.013, the test of shear for adobes without fiber and with fiber, were performed and average values of 5,33 kg cm-2 and 2,73 kg.cm-2 were obtained, respectively. Thermal conductivity for adobe without Stipa ichu and with Stipa ichu were 0,371 W m-1K-1 y 0,349 W m-1K-1 , respectively. According to scanning electron microscopy micrographs of an adobe brick, its internal morphology was highly heterogeneous and porous, which contained particles and cavities of different sizes. The fiber (Stipa ichu) presented a random distribution and was observed closely attached to the surrounding matrix. VI Finally, from XRD studies, it was found that the type of clay presented in the soil used for the fabrication of adobes, was predominantly illite-montmorillonite. Keywords: Biocomposite, Adobe, Stipa ichu, ASTM, X-ray diffraction, Scanning Electron Microscopy, Thermal Conductivity.